(untitled) (Nonconventional Technologies Review, 2025)
The paper presents the current state of the electrochemical polishing process (Electro Chemical Machining – ECM), using the intermittent flow method of the electrolytic liquid. The uniformity of the flow rate on the machined surface was aimed for, a key condition for ECM polishing. The logical scheme of the study and numerical simulations of the flow were developed for three different machining surfaces, in the following cases: laminar flow, turbulent flow and flow stop. The distributions of flow velocities in the machining gap were determined. The results of the simulations were validated by experimental data that determined an optimal value for the current density on the machined surface at which a maximum decrease in roughness was achieved.